Penerapan Konseling Kelompok dengan Teknik Creative Problem Solving untuk Mengurangi Stres Akademik Siswa - Sacania Samma; Imanuel madika langi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This research investigates the impact of Creative Problem Solving (CPS) within a group counseling framework to mitigate academic-related stress in students. Intense scholastic expectations often compromise a student’s psychological health and academic achievements, making this a critical area of intervention. Employing a quasi-experimental quantitative design, this study utilized a single-group pretest-posttest model. Participants exhibiting elevated stress markers were recruited via purposive sampling. The core intervention involved systematic group sessions centered on diagnostic problem-solving, divergent idea generation, and strategic decision-making. Pre- and post-intervention data were gathered through a standardized assessment scale and processed using parametric statistics. The data revealed a substantial decline in academic stress levels post-treatment. These results underscore the efficacy of CPS-based counseling in fostering cognitive flexibility. Ultimately, this approach provides a robust mechanism for students to develop resilient coping strategies against educational pressures.